STUDENT – YOUNGERS’ LEISURE AND CULTURE USE OF IT (World Bulletin of Social Sciences, 2021)
The article deals with the problems of organizing the culture and use of leisure time of youth
Keywords: Leisure; leisure culture; spiritual need; healthy spiritual need